Antecedents of Consumer’s Purchase Intention Towards Energy-Efficient Home Appliances: An Agenda of Energy Efficiency in the Post COVID-19 Era - Jamil, Khalid; Dunnan, Liu; Awan, Fazal Hussain; Jabeen, Gul; Gul, Rana Faizan; Idrees, Muhammad; Mingguang, Liu (Frontiers in Energy Research, 2022)
This study focuses on the energy efficiency in the past COVID-19 era and targeted the young population of Pakistan who are facing the critical situation of COVID-19 era and much aware that this situation will badly affect the energy situation when COVID-19 will end and they also aware that energy efficient appliances will be the most valuable products after the COVID-19 era. Data was collected from five major cities of Pakistan and analyzed by applying structure equation modelling through smart-PLS 3.3. Results show that knowledge of eco-labels has significant impact on perceived functional values, green trust and purchase intention of energy efficient home appliances. Results further indicate that consumers social responsibility has significant impact on personal norms and purchase intention of energy efficient home appliances. Moreover, functional value and green trust mediates the relationship of knowledge of eco-labels and purchase intention of energy efficient home appliances. Furthermore, attitude towards energy efficient appliances mediates the relationship between consumers social responsibility and purchase intention but surprisingly no mediating affect of attitude between consumer social responsibility and purchase intention of energy efficient home appliances. This study presents an antecedent model for predicting energy-efficient home appliances based on consumer awareness. This study will help companies for technology innovation and improvements in the efficiency of household appliances are among the key functional values that companies should emphasize, in order to attract consumers to value the surprising energy-saving effects of appliances.